Association Between Family Structure and Anxiety Disorder Among Pre-schoolers: A Cross-Sectional Study in Urban Chongqing, China - Hu, Hongmei; Wu, Tingting; Wang, Shanshan; Chen, Peiling; Zhang, Jiaqiong; Zhao, Xin (Frontiers in Psychiatry, 2021)
Objective: This study explores the current situation of self-reported anxiety disorder of preschoolers and assesses the association between family structure and self-reported anxiety disorder among preschoolers in Chongqing, China. Methods: This is a cross-sectional study of 499 main fosterer of children aged 3-6 years who completed the 28-item Chinese version of the Spence Preschool Anxiety Scale (PAS). The cut-offs of the PAS were used to derive prevalence. Multinomial logistic regression with three models was used to assess the association of the family structure with the anxiety disorder(AD). Results: The prevalence of AD was 31.46%, whose score of PAS were more than 48. Among the five different PAS sub-scales, the prevalence of obsessive-compulsive disorder (OCD) was the highest (50.10%), followed by separation anxiety disorder (SAD, 39.28%), fear of physical harm (FPH, 37.68%), and generalized anxiety disorder (GAD, 33.47%), and the prevalence of social phobia (SP) was the lowest (25.85%). Preschoolers from different family structures exhibited different prevalence of anxiety disorder (p<0.001). Preschoolers from inter-generational families were more likely to have AD than those from nuclear families (OR=3.73, 95% CI=1.76, 7.89). The participants from inter-generational families were more likely to have SAD (OR=3.39, 95% CI=1.63, 7.04), FPM (OR=2.80, 95% CI=1.39, 5.65), or OCD (OR=2.40, 95% CI=1.16, 5.04), in comparison with participants from other family structures. Additionally, participants from stem families were less likely to have SAD (OR=0.85, 95% CI=0.53, 1.38) but not significantly (p>0.05). Conclusion: Anxiety disorder among preschoolers aged 3-6 in Chongqing is widespread. Preschoolers from inter-generational families were more likely to have AD, SAD, FPM and OR and preschoolers from stem families may be less likely to have SAD compared with those from nuclear families. Relieving the anxiety of preschoolers may be possible with additional interventional efforts in inter-generational families.